PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL LEARNING MELALUI MEDIA KARTOPAN TERHADAP PEMAHAMAN DAN KEMANDIRIAN SISWA KELAS 5A MATA PELAJARAN PENDIDIKAN PANCASILA DI UPTD SDN PEJAGAN 1 BANGKALAN - Lailatul Qomariyah; Yunita Hariyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to determine the effect of using the contextual learning model on students' understanding and learning independence at UPTD SDN Pejagan 1 Bangkalan in Pancasila education. This study used a quantitative approach with a one-group pretest-posttest design. The population in this study consisted of all 21 students in class 5A. The instruments used in this study were questions and questionnaires. The analysis tests used were validity tests to determine the validity of the instrument data, reliability tests to determine the consistency level of the valid instruments, normality tests to determine whether the distribution of the instrument data was normal or not, and paired sample t-tests to determine the difference in the mean of the data of two variables from two samples using the SPSS application. This can be proven in the use of the contextual learning model through the use of kartopan media in Pancasila education, which has a significant effect on students' understanding and learning independence based on the analysis results of a sig. value of 0.000 < 0.05.